Influence of Gas Sort on the Nucleation Region Width of Si Nanocrystal Grains Prepared by Pulsed Laser Ablation. (30th March 2014) - Deng, Zechao; Chu, Lizhi; Ding, Xuecheng; Qin, Aili; Fu, Guangsheng; Wang, Yinglong
Abstract : We have calculated the nucleation region (NR) location of Si nanocrystal grains prepared by pulsed laser ablation (PLA) with fluence of 4 J/cm 2 in 10 Pa gas at room temperature, and ambient gases were He, Ne, and Ar, respectively. Results of calculation indicated that NR width in Ne gas was narrowest, while it was widest in He gas. Maximum mean size of grains deposited on substrates under ablated spot, which were placed horizontally, was the smallest in Ne gas. It would be attribute to more effective energy transfer during the process of collision when atomic mass of Si and ambient gas Ne are more close to each other. In this work, an additional gas flow with the same element as ambient gas was introduced, which is vertical to the plume axis at different lateral positions above ablated spot.